Lichens GO. Sociologie d’une métrologie citoyenne de la qualité de l’air - Vincent Abensour; Florian Charvolin; Laure Turcati (Développement Durable et Territoires)
Lichens Go! is a French citizen science observatory monitoring air quality through recording lichens as bioindicators. Following a test phase during spring 2017 we discuss here the diversity of motivations to be involved in such observatory and its development. We also explore the relationship between lichens and the participants and the potential impact on their habits and perception of air quality. Finally we explain the usefulness of such a test phase for this citizen sciences project.